Efectos sociopolíticos de la construcción de la hidroeléctrica urrá i en la comunidad indígena embera catío (colombia) (2010)
The Embera Catio people live in the Nudo de Paramillo (HighSinu River, Western Mountain Chain at Colombian Andes)since ancient times. Despite the circumstances that have surroundedthem, they retain part of their culture and have soughtto keep their forms of government and social relationships thatgovern life in community. However, the construction of theUrra I hydroelectric encountered the Embera Catio with thedeterioration of a significant part of their territory, losing sacredsites and lands for cultivation, as well as the emergence of socialconflicts they were previously unaware of. This situation forcedthe Indigenous group to change its social and organizationalbehavior, and to adapt to new environmental conditions. Thiswork shows a parallel between before and after the constructionof the Urra I hydroelectric and subsequent effects on social andpolitical organization brought by the river damming.